Mechanical drawing : CAD-communications - French, Thomas Ewing, 1871-1944. (New York : Gregg Division, McGraw-Hill, 1990)
A textbook introducing the basic theory, techniques, and uses of drafting for industrial arts and vocational high school students.
Includes index.
Keywords: Mechanical drawing; Mechanical drawing